Vous avez dit paléogénomique ? - Céline Bon; Marie-Claude Marsolier-Kergoat (Revue d'ethnoécologie)
Palaeogenomics is a recent discipline that studies the genomes of ancient individuals. Since its appearance in 2001, it has widely expanded, addressing increasingly ambitious themes, from the reconstruction of extinct animals' genomes of to the inference of migration and mixing processes among humans. We explain its contributions to different disciplines (study of evolution, archaeology, etc.) and then describe some of the past or current studies we have participated in or are currently conducting.